Capitalism in Chaos : How the Business Elites of Europe Prospered in the Era of the Great War - Rigó, Máte, 1985- (Book collections on Project MUSE., 2022)
"This book is about the survival of industrial families in Western and East-Central Europe despite the First World War and collapse of the Austro-Hungarian and German empires. More specifically, the book draws on case studies of industrialists in Alsace-Lorraine and Transylvania that speak to French, German, Austro-Hungarian and Romanian history more generally between 1867 and 1928"--